F Is for Freedom - Schotter, Roni; Nang Chan Yeema (New York, USA Scholastic Inc., 2000)
Amanda's house is a stop on the Underground Railroad. When a family of runaway slaves hides in her home, Amanda quickly becomes friends with their daughter, Hannah. When Amanda takes Hannah outside for a taste of freedom, slave hunters spot the girls.
Keywords: Adult Fiction